Internetworked world : 15th Workshop on e-Business, WeB 2016, Dublin, Ireland, December 10, 2016, Revised selected papers /: 15th Workshop on e-Business, WeB 2016, Dublin, Ireland, December 10, 2016, Revised selected papers. (2017) - Unknown
No abstract available